Out‐of‐Hospital Cardiac Arrests and Wildfire‐Related Particulate Matter During 2015–2017 California Wildfires. Issue 8 (21st April 2020) - Jones, Caitlin G.; Rappold, Ana G.; Vargo, Jason; Cascio, Wayne E.; Kharrazi, Martin; McNally, Bryan; Hoshiko, Sumi; ,
Abstract : Background: The natural cycle of large‐scale wildfires is accelerating, increasingly exposing both rural and populous urban areas to wildfire emissions. While respiratory health effects associated with wildfire smoke are well established, cardiovascular effects have been less clear. Methods and Results: We examined the association between out‐of‐hospital cardiac arrest and wildfire smoke density (light, medium, heavy smoke) from the National Oceanic Atmospheric Association's Hazard Mapping System. Out‐of‐hospital cardiac arrest data were provided by the Cardiac Arrest Registry to Enhance Survival for 14 California counties, 2015–2017 (N=5336). We applied conditional logistic regression in a case‐crossover design using control days from 1, 2, 3, and 4 weeks before case date, at lag days 0 to 3. We stratified by pathogenesis, sex, age (19–34, 35–64, and ≥65 years), and socioeconomic status (census tract percent below poverty). Out‐of‐hospital cardiac arrest risk increased in association with heavy smoke across multiple lag days, strongest on lag day 2 (odds ratio, 1.70; 95% CI, 1.18–2.13). Risk in the lower socioeconomic status strata was elevated on medium and heavy days, although not statistically significant. Higher socioeconomic status strata had elevated odds ratios with heavy smoke but null results with light and medium smoke. Both sexes and age groups 35 years and older were impacted on days with heavy smoke. Conclusions: Out‐of‐hospital cardiac arrests increased with wildfire smoke exposure, and lower socioeconomic status appeared to increase the risk. The future trajectory of wildfire, along with increasing vulnerability of the aging population, underscores the importance of formulating public health and clinical strategies to protect those most vulnerable.